The impact on school improvement due to indulgence of Monitoring & Evaluation Assistants (MEAs) in district Pakpattan, Pakistan - Aryan Asad; Muqaddas Rani; Tahira Gulshan; Dr. Khalid Mahmood Arif; Rizwana Bashir Zia (Al-Qanṭara, 2023)
The assessment methods used by Monitoring and Evaluation Assistants at the elementary school level in District Pakpattan are examined in the current research. The study's main goal was to assess how Monitoring and Evaluation Assistants affected many aspects of school improvement, including teacher and student presence, provision of excellent teaching, infrastructure, and enrollment drive performance. All of the public sector's heads of primary schools made up the study's sample. A sample of sixty head teachers from District Pakpattan was used. Heads of elementary schools received one questionnaire with a five-liker rating system that was self-created. The information was gathered through personal visits and a five-liker scale questionnaire. The information was gathered and entered into SPSS. Chi-square testing and percentages were used to analyze the data. Research revealed that HTs concurred that MEAs increased the effectiveness of government primary schools. The analysis of the data revealed some significant findings, including the improvement of teacher attendance, school infrastructure, student cleanliness, student sanitation, record-keeping, student enrollment, and student attendance. The government must maintain digital records of every teacher it employs, recognize accomplishments, and put in place a suitable evaluation system. In order to improve the effectiveness of the monitoring system, the government must provide MEA employees with all the resources they require.